Serum magnesium in pregnancy induced hypertension - Bandebuche, Sanjyoti; Sagade, Bhushan; Sontakke, Alka N. (International Journal of Research in Medical Sciences, 2017)
Background: PIH is a major cause of maternal & perinatal morbidity & mortality worldwide because of its complications. The etiology of PIH is uncertain but appears to be related to uteroplacental ischaemia. Magnesium is one of the principle macronutrients, regulates vascular tone, causes relaxation of muscles of uterus and decreases excitability of nerves & muscles. Hence the study was planned to estimate and compare the levels of magnesium between women with PIH and normal pregnant women. Methods: The study comprised of thirty clinically diagnosed PIH patients and thirty gestational age-matched controls. Serum magnesium was estimated spectrophotometrically. Results: Significant decrease was observed in magnesium levels in women with PIH as compared to normal pregnant women. Conclusion: The decreased serum magnesium levels may indicate its possible role as one of the risk factors in the development of PIH in pregnant women. Hence the screening of clinically diagnosed cases of PIH for hypomagnesemia may help in minimizing the complications of PIH. Hypomagnesemia could be treated with magnesium supplementation and follow up of the patients for complications would be necessary to comment further.